Zarco Moniz Ferreira and the Portuguese far right between authoritarianism and democracy: A biographical approach - Marchi, R.; Pinto, T. (Locus: Revista de História, 2022)
In the 1960s and 1970s, Portugal witnessed a cycle of political radicalisation on the right and left, in the context of the crisis and fall of the authoritarian Salazarist regime, and the transition to democracy after the military coup of 1974. For the right wing, radicalisation was led by young university students inspired by the Portuguese nationalism of the first half of the 20th century, but also by foreign doctrines from the inter-war period, and by the neo-fascist subculture immediately afterthe second world war. This article explores the mobilisation of this radical subculture, with its links to the Estado Novo and the European far right, through a bibliographical appreciation of one of its best-known leaders, nationally and internationally:Zarco Moniz Ferreira. From his career as a political activist, between the end of authoritarianism and the democratic transition, a faithful picture emerges of the characteristics, dynamics, successes and failures of the mobilisation of the far-right in those troubled years of recent Portuguese history.